Agricultura por ambiente: manejo sítio específico da população de milho - Hörbe, Tiago de Andrade Neves (2012)
Precision agriculture (PA) is based on site-specific interventions, according to the spatial variability of productive factors. This strategy tends to decrease the spatial variability of yield in relation to that obtained with the uniform management and optimize the resources used. The objective of this study was to assess the population of corn plants using as a parameter, management zones. Thus, the work was composed of two experiments conducted in different locations and crop years, the municipality of Non-Touch-Me-RS, and experimental areas close together. In experiment 1 (A), conducted in 2009/2010, management zones were delineated through knowledge of the production history through observations of the farmer, separating the plot of study in areas of low (ZB), medium (ZM ) and high productivity (ZA). As for the second experiment (B) in 2010/2011 harvest yield maps standard nine (seven + two crops of soybeans, maize) were superimposed generating three management zones. The areas were classified as presenting relative productivity ZB <95% of the average productivity of the crop, ZM between 95-105 and ZA > 105%. The experiment was a factorial with five seeding rates ranging from 50,000 to 90,000 seeds ha-1 consists of three management zones (ZB, ZM and ZA) under Oxisol. For the second experiment, was added as an assessment of the effect of setting the maize population management zones and their relation to the demand of N by the crop, using as parameter the readings with chlorophyll and N in dry matter in full bloom culture. In both experiments, the maize population was related to productivity in the areas of management, with a correlation coefficient of 0.89 (p> 0.0004), 0.81 (p> 0.0002), 0.97 (p > 0.0002) for ZB, ZM and ZA, respectively. The adjustment of the population of maize plants, parts management provided increases in productivity as compared with the fixed population (70,000 plants ha-1). This increase in ZB due to reduction of the population, Mg is 1.20 h -1 and 1.90 h-1 Mg, resulting in increased economic 19.8 and 28.7% for (A) and (B ), respectively. In the ZA, due to increased population, increased production was 0.89 Mg ha-1 and 0.94 Mg ha-1 providing an economic growth of 5.6 and 6.6% for (A) and (B ), respectively. Evaluations of N in the second experiment, the population growth of maize ZB caused a decrease of 49% for the evaluation of chlorophyll and 44% for N absorbed compared to ZA. However the adjustment of the maize population led to a better use of N fertilizer, and the increase in N uptake by corn of 8.40 and 15% in ZA and ZB when compared to fixed population of 70,000 plants ha-1.